2012
DOI: 10.1007/s12288-012-0165-8
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Screening for β Thalassemia in Pregnant Indian Women: Experience at a Single Center in Madhya Pradesh

Abstract: To study the prevalence of b thalassemia trait in pregnancy in urban population screening for b thalassemia in pregnant women at a single center in Indore (MP) has been conducted for a period of 2 year. Blood samples were tested for complete blood count and hemoglobin electrophoresis. During the 2 year period a total of 1,006 women were screened; 28 women who carried abnormal pattern were detected. The mean gestational age for screening was 13 ± 4 weeks. The prevalence of carriers was 2.78 %. As much as 99 % o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 9 publications
1
19
1
Order By: Relevance
“…This was followed by HbE trait, beta-thalassemia major and other abnormal hemoglobin types. A single-center study in central India which undertook population screening estimated the prevalence of betathalassemia carrier state to be around 2.78% [4]. A slightly higher prevalence of abnormal hemoglobin types may be found in rural areas [5].…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by HbE trait, beta-thalassemia major and other abnormal hemoglobin types. A single-center study in central India which undertook population screening estimated the prevalence of betathalassemia carrier state to be around 2.78% [4]. A slightly higher prevalence of abnormal hemoglobin types may be found in rural areas [5].…”
Section: Discussionmentioning
confidence: 99%
“…Asha Baxi et al also reported similar results in their study conducted in Indore during a period of 2 years. 4 Lack of education and general unawareness about the disease makes husbands of carriers reluctant to get themselves screened for the disease as was also reported by Colah et al 15 HbD famous by the label of HbD Los Angeles is usually detected in North-Western India. Still some sporadic cases have been reported from Gujarat.…”
Section: Discussionmentioning
confidence: 96%
“…This is only possible by screening and counseling. 4 Cao A et al observed a significant reduction in the birth rate of thalassemia Major cases from 1:250 to1:4000 live births. 18 This requires massive screening and robust counseling.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Financial barriers were reported to be a common hindrance to patients' acceptance and utilization of genetic services. 41,50,69,78,80,85,89,91,95,102,116,119,[125][126][127][128][129][130][131][132][133][134] Although insurance coverage and subsidies paid by the government in some LMICs improve access to these services, high cost of genetic services remains a barrier, especially for low-income and rural patients. 83,116,125,[135][136][137] When genetic services are not widely available, patients often must travel long distances to access them, incurring high costs.…”
Section: Ethical Issuesmentioning
confidence: 99%